A Mixed-Methods Study of Marketing Students’ Game-Playing Motivations and Gamification Elements - Jaskari, Minna-Maarit; Syrjälä, Henna (Sage Publications, 2022)
In this article, we examine the linkage between students’ game-playing motivations and a wide variety of gamification elements within higher marketing education. Using an interpretive and convergent mixed-methods design, we discover four clusters of students that vary in terms of their game-motivational bases and views on gamification elements. Social completionists want to study together with others and enjoy the social aspects of gamification. Highly motivated completionists could be described as ambitious students who enjoy social learning but are also internally motivated and willing to accept most gamification elements. Independent completionists want to immerse themselves in learning but prefer the individual and noncompetitive elements of gamification. Pure completionists are the “let’s get it done” group, who want to focus on completing their studies and are likely to be critical toward any gamification. We propose that higher education should take into account the differences in students’ game-playing motivations and fine-tune their gamification efforts to engage and motivate different kinds of students. Finally, we provide suggestions to marketing educators on how to consider the various motivational bases of the participants in gamified experiences.
Keywords: cluster analysis; game-playing motivations; higher education; marketing education; mixed-method; gamification; fi=Markkinointi|en=Marketing|